(untitled) (International relations and international law Journal, 2016)
The article deals with the establishment of diplomatic relations between the Republic of Kazakhstan and the People’s Republic of China and its development till present time. The author indicates prerequisites and reasons of establishment of diplomatic relations between the Republic of Kazakhstan and the People’s Republic of China. The article contains important information on Kazakh-Chinese relations.